Fungal Diversity in Multiple Post-harvest Aged Red Pine Stumps and Their Potential Influence on Heterobasidion Root Rot in Managed Stands Across Minnesota - Otto, Eric C.; Held, Benjamin W.; Gould, Trevor J.; Blanchette, Robert A. (Frontiers in Fungal Biology, 2021)
Thinning operations that occur in managed red pine (Pinus resinosa) stands, create tree stumps that can serve as a habitat for fungi, especially Heterobasidion irregulare, the cause of a serious root disease. Different fungi can colonize stumps early and the community of fungi can change over time as initial fungal species become replaced. Samples were collected from both the native and non-native range of red pine from stumps that were cut at different time periods. Stumps that were harvested at 0–1, 2–3, 5–6, and 10–12 years before sampling were used to provide data on the diversity of fungi that colonize tree stumps and how these communities can change over time as well as how they influence colonization of H. irregulare. Traditional culturing methods and Illumina MiSeq sequencing were used to identify the fungi in the samples. Of particular interest was Phlebiopsis gigantea, which can colonize cut stumps and prevent H. irregulare from becoming established. Overall, P. gigantea was the most abundant fungus isolated and sequenced via Illumina MiSeq. Results show that Phlebiopsis gigantea was isolated from 90% of all stumps sampled for sites harvested within 3 years of sampling in the native range of red pine compared to 33% in the non-native range. For Illumina MiSeq, 5,940 total amplicon sequence variants (ASVs) were detected. P. gigantea represented 14% of the total reads and composed 19% of the reads in the native range and 8% in non-native range of red pine. Furthermore, P. gigantea represented 38% of the reads for stumps that were harvested within 3 years of sampling in the native range of red pine compared to 14% in the non-native range. These results help demonstrate that a higher amount of P. gigantea is present in the native range of red pine and could be acting as a native biological control agent. Additional fungi, including Resinicium bicolor, Hypochnicium cremicolor, Leptographium spp., and others identified at different cutting times are also discussed. Finally, different diversity indices revealed similar, but slightly higher diversity for southern sites via Shannon and Simpson Diversity indices. Beta diversity demonstrated a similar species composition in stumps harvested at different times with these stumps being grouped together based on harvesting years.